The Role of Customer Satisfaction as an Intervening Variable between Servicescape and Repurchase Intention: A Study on Maxx Coffee Customers in Medan - michael novranda Surbakri; Iventura Fitra Uli Tamba; Trans Ningsih; Agusman (Journal Of Management Analytical and Solution (JoMAS), 2025)
Nowadays, cafes that serve coffee drinks are competing with one anotherextremely quickly. Understanding customer behavior is one strategy to win thecompetition. For instance, keeping an eye on customer satisfaction and theservicescape of their workplace. The aim of this research was to evaluate andascertain how Servicescape and Customer Satisfaction directly affectRepurchase Intention, as well as how Customer Satisfaction functions as anintermediate variable. A sample of 150 respondents was used in the descriptiveassociative research design. Using the Smart PLS application, the data analysistechnique is (Partial Least Square) PLS. The findings revealed that Servicescapeand Customer Satisfaction have a positive and significant effect on RepurchaseIntention; Servicescape has a positive and significant effect on CustomerSatisfaction; and Servicescape has a positive and significant effect onRepurchase Intention via Customer Satisfaction at Customer Maxx Coffee inMedan. The R-squared value for the variable of repurchase intention is 0.786,whereas the variable of customer satisfaction is 0.684. The acquisition of thesevalues explains that the percentage of large intention to repurchase can beexplained by servicescape and customer satisfaction of 78.6%, while theacquisition of the value that explains the percentage of the large performance ofcustomer satisfaction can be explained by servicescape of 68.4%.